Penguatan Pastoral Mahasiswa Melalui Rekoleksi Sebagai Ruang Refleksi Panggilan Hidup Orang Muda Katolik - Bhakti, Angga Satya; Kurniati, Yusi; Zulkarnain, Rezkie; cenderato, Cenderato; Ismarjo, Alblikus Eko (Abdimas Mandalika, 2026)
Abstract:  This community service activity aimed to strengthen the spiritual identity of Catholic university students, deepen their understanding of their calling as Catholic Youth (Orang Muda Katolik/OMK), enhance their active involvement in church ministry, and cultivate a genuine spirit of evangelization. The program was carried out through a recollection activity employing the Asset Based Community Development (ABCD) approach, guided by five successive stages: discovery, dream, design, define, and destiny, involving Catholic students from five universities across the city of Pontianak. The recollection proved fruitful in several meaningful ways. Participants gained a clearer and more heartfelt understanding of who they are as Catholic Youth. They also grew in awareness of the importance of being actively engaged in their church communities and felt a deeper sense of calling to serve others. Beyond that, a shared commitment emerged among participants to support one another in their faith journey, as well as a sincere resolve to proclaim the teachings of Christ, including through social media platforms. Overall, the ABCD-based recollection demonstrated its effectiveness as a spiritual formation model that is not only structured and contextual, but also deeply relevant and transformative for Catholic university students.Abstrak:  Pengabdian kepada masyarakat ini bertujuan untuk menguatkan jati diri spiritual mahasiswa Katolik, memperdalam pemahaman mereka akan panggilan hidup sebagai Orang Muda Katolik (OMK), meningkatkan keterlibatan dalam pelayanan gerejawi, serta menumbuhkan semangat evangelisasi. Kegiatan dilaksanakan melalui rekoleksi dengan pendekatan Asset Based Community Development (ABCD) yang berjalan melalui tahapan discovery, dream, design, define, dan destiny, melibatkan mahasiswa Katolik dari lima perguruan tinggi di wilayah Kota Pontianak. Hasil dari rekoleksi ini ialah para peserta menjadi paham akan jati diri mereka sebagai Orang Muda Katolik. Para peserta juga semakin sadar akan pentingnya keterlibatan aktif dalam komunitas gerejawi dan merasa lebih terpanggil untuk melayani. Selain itu, tumbuh pula kesadaran bersama untuk saling menopang dalam perjalanan iman serta komitmen nyata untuk mewartakan ajaran Kristus, termasuk melalui media sosial. Rekoleksi berbasis ABCD terbukti menjadi sarana pembinaan rohani yang efektif, kontekstual, dan bermakna bagi mahasiswa Katolik.